Amphibia, Anura, Brachycephalidae, Brachycephalus hermogenesi (Giaretta and Sawaya, 1998): new species record in the state of Paraná, southern Brazil and geographic distribution map - Adriele Karlokoski Oliveira; Igor Oliveira; Marília Hartmann; Nelson Silva; Luís Toledo (Check List, 2011)
Currently, the distribution of Brachycephalus hermogenesi (Giaretta and Sawaya, 1998) ranges from the state of Rio de Janeiro to the state of São Paulo. Herein, we report for the first time the occurrence of B. hermogenesi in the state of Paraná, southern Brazil.